The Transformation of Islamic Finance in the Digital Era: Opportunities and Challenges for Muslim Communities - Samsul Muarif; Andriani Samsuri (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2026)
This article aims to discuss the transformation of Islamic finance in the digital age by examining the opportunities and challenges it presents for Muslim communities. This study employs a qualitative approach using library research methods, involving an analysis of books, journal articles, official documents, regulations, fatwas, and scientific publications related to Islamic finance, the digital economy, Sharia fintech, digital Sharia financial literacy, and maqāṣid al-sharī‘ah. The study’s findings indicate that digital Islamic finance presents significant opportunities to expand access to Sharia-compliant financial services, enhance financial inclusion, support the development of halal SMEs, and optimize the management of zakat, infak, sedekah, and waqf through digital platforms. However, this transformation also faces challenges such as low digital Sharia financial literacy, data security risks, the public’s limited understanding of contracts, Sharia compliance, regulations, and users’ ethical awareness. Therefore, the strengthening of digital Islamic finance must be achieved through improved public literacy, Sharia oversight, adaptive regulations, consumer protection, and collaboration among the government, Sharia financial institutions, religious scholars, academics, educational institutions, and digital industry players. This article emphasizes that digital Islamic finance is not merely a form of financial service modernization but also a vital instrument in building an inclusive, secure, just, and public-interest-oriented economy for the Muslim community.